2015
DOI: 10.1177/0001699315605161
|View full text |Cite
|
Sign up to set email alerts
|

Can you stay home today? Parents’ occupations, relative resources and division of care leave for sick children

Abstract: This is one of only a few studies on the division of care leave for sick children (temporary parental leave) between parents in Sweden and is the first to examine the importance of differences in parents' work characteristics. The study uses register data for parents with children born between 1999 and 2002 to analyse two aspects of parents' employment that may be of importance for the division of care leave: their relative resources, in this case wages, and different occupations. First, the results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…However, our results do not suggest income division within couples being a strong predictor of the division of childcare within parental couples of children with cancer, as the associations found were few and modest. These results do not give much support for the theory of relative resources on the division of childcare among parents of seriously ill children, thus deviating from studies on parents in the general Swedish population (Amilon, 2007;Boye, 2015a). Our results suggest that other gender-related factors may be influential in explaining the unequal division found between mothers and fathers of seriously ill children, which have been indicated in previous studies on parents in the general population as well (Amilon, 2007;Nitsche & Grunow, 2018;Raley et al, 2012).…”
Section: Discussioncontrasting
confidence: 97%
“…However, our results do not suggest income division within couples being a strong predictor of the division of childcare within parental couples of children with cancer, as the associations found were few and modest. These results do not give much support for the theory of relative resources on the division of childcare among parents of seriously ill children, thus deviating from studies on parents in the general Swedish population (Amilon, 2007;Boye, 2015a). Our results suggest that other gender-related factors may be influential in explaining the unequal division found between mothers and fathers of seriously ill children, which have been indicated in previous studies on parents in the general population as well (Amilon, 2007;Nitsche & Grunow, 2018;Raley et al, 2012).…”
Section: Discussioncontrasting
confidence: 97%
“…In couples, the division of caregiving responsibilities is often skewed, with women assuming a caregiving role more often than men due to gendered norms and habits. 14,15 Also, economists and sociologists have suggested economists and sociologists have suggested that the decision regarding which parent takes the caregiving role also may relate to the balance of bargaining power (of each individual). [13][14][15] By assuming informal caregiving responsibilities, mothers may change their profession or reduce work responsibilities to spend more time at home; they also may experience reduced motivation for work and passion for their career.…”
Section: Income and Social Benefits Trajectories/hiyoshi Et Almentioning
confidence: 99%
“…14,15 Also, economists and sociologists have suggested economists and sociologists have suggested that the decision regarding which parent takes the caregiving role also may relate to the balance of bargaining power (of each individual). [13][14][15] By assuming informal caregiving responsibilities, mothers may change their profession or reduce work responsibilities to spend more time at home; they also may experience reduced motivation for work and passion for their career. 4,29 Lost opportunities for promotion and career options may exert a lasting impact on earnings.…”
Section: Income and Social Benefits Trajectories/hiyoshi Et Almentioning
confidence: 99%
“…Thus, the studies examined in this section include fathers irrespective of their work hours. Researchers examining the ways mothers' employment can shape fathers' involvement with children often draw upon the time availability and relative resources theoretical perspectives (Aassve et al, 2014;Boye, 2015;Nitsche & Grunow, 2018). These theories demonstrate how time, economic, and educational resources are key mechanisms that explain fathers' participation in childcare.…”
Section: Mothers' Employment and Fathers' Participation In Childcarementioning
confidence: 99%
“…The relative resources perspective was originally applied to understanding gendered divisions in paid and unpaid labour. Despite this, for a number of years now, it has also often been adapted to understanding the gendered differences in childcare and paid labour (Boye, 2015;Bulanda, 2004;Craig & Mullan, 2011;Nitsche & Grunow, 2018;Raley et al, 2012). For example, Nitsche and…”
Section: Parents' Income and Its Association With Fathers' Participatmentioning
confidence: 99%